Efektivitas Pembelajaran Pendidikan Agama Islam Dalam Meningkatkan Kualitas Akhlak Siswa Kelas VII SMPN 3 Bayongbong - Sulaiman, Husnan; Dhulyaden, Maden Ahmad (STAI Al-Musaddadiyah Garut, 2022)
This research was initiated in response to the observation of students exhibiting poor behavior, such as neglecting prayer, lacking discipline, dishonesty, and irresponsibility. These issues are attributed to the suboptimal effectiveness of Islamic Religious Education (PAI) in enhancing students' moral quality, leading to a decline in their moral standards. This moral degradation is pervasive across all sectors of human life, including among students, who represent the younger generation. The aims of this study are to describe: (1) the moral quality of seventh-grade students at SMPN 3 Bayongbong; (2) the effectiveness of PAI instruction in seventh-grade classes at SMPN 3 Bayongbong; and (3) the supporting and inhibiting factors affecting the effectiveness of PAI instruction in improving the moral quality of seventh-grade students at SMPN 3 Bayongbong. This research employs a descriptive method, with data collection techniques including observation, in-depth interviews, and documentation studies. Data analysis involves steps of data reduction, data presentation, and conclusion drawing. The findings indicate that while the effectiveness of PAI instruction in enhancing students' moral quality has been achieved, it has not yet reached its full potential. The approach taken by teachers to improve the moral quality of students through effective PAI instruction involves various strategies. These include a persuasive approach both inside and outside the classroom, collaboration with community leaders to provide non-formal education outside school hours, implementing short-term Ramadan boarding programs with incentives for participation, and using constructive authority and guidance to steer student behavior towards positive outcomes. Keywords: Effectiveness of PAI Instruction, Moral Quality of Students